Johnson, British Imperialism - Voeltz, Richard (Teaching History: A Journal of Methods, 2005)
This handy book, as the series title indicates, "aims to explain some of the histories and controversies about British Imperialism. It offers an introduction, critical analysis, and overview of the debates that surround the British Empire from its origins to the return of Hong Kong to Chinese rule in 1997 ." The author is also aware of the debate between those who claim to be "Imperial Historians" and those who see themselves as post-colonial theorists and subaltern scholars. Frequent references are made to the recently published, monumental Oxford History of the British Empire but not to the Companion Series.